Role of zinc oxide on rheology of thermosensitive gel developed for periodontitis treatment - J. Mahadlek (2018)
Periodontal disease is a major cause of tooth loss, therefore a more recent approach such as thermosensitive gel is loaded with antimicrobial drugs to be delivered locally to the periodontal pocket. The effect of ZnO on thermosensitive gel properties including gelation-gel melting temperature, rheology, syringeability, and the release behavior of antimicrobial drug such as doxycycline hyclate were investigated. The increased amount of ZnO apparently decreased the gelation temperature of the Lutrol® F127 system. Syringeability of the doxycycline hyclate-Lutrol® F127 systems were increased with the increased amount of ZnO. System comprising zinc oxide could prolong the release of doxycycline hyclate from Lutrol® F127 systems and could be delivered from a syringe through a needle for utilizing in periodontitis therapy at the periodontal pocket. © (2010) Trans Tech Publications.